2013
DOI: 10.1179/1743132813y.0000000216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the anxiolytic and sedative profile of JM-20: a novel benzodiazepine–dihydropyridine hybrid molecule

Abstract: These results indicate that JM-20 has an anxiolytic profile similar to DZP and its dihydropyridine moiety did not appear to interfere with the GABAergic activity associated with benzodiazepine. Furthermore, JM-20 did not show significant acute toxic effects in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In fact, various studies have shown that zebrafish respond similar to mammals when treated with many pharmacological compounds [27][28][29]. For example, benzodiazepine medication causes sedative effects in mouse [30,31] and zebrafish [32]. For caffeine, it is not different: both rodents and zebrafish present anxiety-like behavior following caffeine exposure [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various studies have shown that zebrafish respond similar to mammals when treated with many pharmacological compounds [27][28][29]. For example, benzodiazepine medication causes sedative effects in mouse [30,31] and zebrafish [32]. For caffeine, it is not different: both rodents and zebrafish present anxiety-like behavior following caffeine exposure [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the response of animals to a compound is tested in both the LDB and the open field, an increase in LDB-light in the absence of a change in locomotor activity in the open field would suggest that the investigated compound has a specific anxiolytic effect, but no sedative effect, which is highly desirable in anxiolytics especially from a translational perspective (82)(83)(84). Upon literature review, we have found as many records in which the open field was performed as a test of locomotor activity (80,81,85,86), as we have found records in which it was performed as a test of anxiety (87)(88)(89)(90). Here, we identify an issue with the continuation of such tests as long-held standards that may not be appropriate, due to the researcher's degree of freedom in the interpretation of the test's meaning (91,92).…”
Section: Discussionmentioning
confidence: 96%
“…Compounds and reagents JM-20 was synthesized, puri ed, and characterized as previously reported [22], in Analytic Chemistry Laboratory of CIDEM. All general chemicals used were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…starting on 15th day after the beginning of AlCl 3 treatment and until the end of the study. The dose range was selected based on previous experience [22]. To eliminate possible interactions, administration between these two compounds was staggered 30 minutes.…”
Section: Experimental Designmentioning
confidence: 99%